Overexpression of lncRNA SLC16A1-AS1 Suppresses the Growth and Metastasis of Breast Cancer via the miR-552-5p/WIF1 Signaling Pathway - Jiang, Bin; Xia, Jie; Zhou, Xudong (Frontiers in Oncology, 2022)
Background: Breast cancer (BC) is the most common cancer and the 5th leading cancer mortality with 685,000 deaths worldwide in 2020. Long noncoding RNAs (lncRNAs) are critical in BC carcinogenesis and progression. However, the functional roles and mechanisms of SLC16A1-AS1 in BC are unknown. Methods: The expression profile of SLC16A1-AS1 in BC patients was investigated using the data from the Cancer Genome Atlas (TCGA) database, and checked in 80 BC patients, followed by analyzing prognostic value of SLC16A1-AS1 in 80 BC patients. Biological functions of SLC16A1-AS1 were further examined in vivo and in vitro after overexpression of SLC16A1-AS1 in BC cells; possible binding sites between SLC16A1-AS1 with miR-552-5p were predicted by miRDB, between miR-552-5p and Wnt inhibitory factor-1(WIF1) were predicted by miRanda, which were confirmed using dual-luciferase reporter assay with mutation; Spearman correlation assay was applied to evaluate association between genes; rescue experiments were further applied to investigate involved molecular mechanisms. Results: Lower SLC16A1-AS1 expression in BC tissues was related with poor prognosis of BC patients. Upregulation of SLC16A1-AS1 suppressed BC cell viability, colony formation, invasion and migration in vitro and growth in vivo via sponging miR-552-5p to release WIF1. Conclusion: SLC16A1-AS1 is a tumor-suppressor in BC, and lower SLC16A1-AS1 expression is an indicator of poor prognosis in BC patients. SLC16A1-AS1 inhibits BC carcinogenesis and progression via SLC16A1-AS1/miR-552-5p/WIF1 pathway. SLC16A1-AS1 represents a novel diagnostic, therapeutic and prognostic target for BC management.